Existence and Lyapunov Stability of Periodic Solutions for Generalized Higher-Order Neutral Differential Equations. (19th July 2010) - Ren, Jingli; Cheung, Wing-Sum; Cheng, Zhibo
Abstract : Existence and Lyapunov stability of periodic solutions for a generalized higher-order neutral differential equation are established.